Advancing mathematical representation abilities through scientifically-oriented contextual learning modules in junior secondary education - Rizki Wahyu Yunian Putra; Riyama Ambarwati; Abi Fadila (CV. FOUNDAE, 2025)
Background: Many students face difficulties in expressing mathematical ideas due to the absence of instructional materials that connect lessons with real-world contexts. Applying a contextual approach aligned with scientific inquiry may improve students’ conceptual understanding and engagement.Aims: This research seeks to develop and assess the effectiveness of contextual teaching modules designed using a scientific framework to strengthen the mathematical representation skills of junior secondary learners.Methods: Adopting the ADDIE instructional design model, this study utilized a Research and Development (R&D) methodology involving 87 seventh-grade students from two Indonesian schools. Data collection included expert validation instruments, learner feedback surveys, and pretest-posttest measurements, with analysis based on validity, practicality, and effect size metrics.Results: Expert evaluations confirmed high validity, with average ratings of 3.71 for content and 3.73 for media. Student feedback indicated high engagement across both trial groups (mean scores above 3.3). Effect size analysis showed substantial learning gains, with Cohen’s d values of 0.82 and 0.96, indicating strong impact on students’ mathematical representation ability.Conclusion: The contextual modules developed through this study, when implemented with a scientific approach, were validated as effective tools for improving students’ ability to represent mathematical concepts. These outcomes underscore the value of integrating contextual and inquiry-driven strategies into teaching practices to make abstract content more accessible and meaningful in mathematics education.